Paradigm shift in infection control practices in dental clinics in response to COVID-19 among dental professionals in Thailand - Amnuaiphanit, Phisut; Thumbuntu, Thanasak; Gaewkhiew, Piyada; Ampornaramveth, Ruchanee Salingcarnboriboon (Frontiers in Oral Health, 2022)
Infection control (IC) practice routines depend mainly on knowledge, perception, and awareness of a disease among dental professionals. However, there has been no report on the perception, awareness, and adaptability to the new practice guidelines of Thai dental professionals (dentists, dental nurses, dental assistants, and dental technicians) to the COVID-19 pandemic. This study aims to investigate how dental professionals in Thailand perceive and are aware of COVID-19, and how they have changed their IC practices in response to the pandemic. Online cross-sectional surveys using convenience sampling during September 2021 were sent to Thai dental professionals. The data were analyzed using descriptive statistics and the Chi-square test. Statistical analysis was performed using the Statistical Package for Social Sciences, version 22.0. The tests were two-tailed, with a significance level of p < 0.05 and 95% confidence intervals (CIs). The 1,177 dental professionals who completed the questionnaire were from the public and private sectors. Most respondents obtained their knowledge about COVID-19 from social media (91.8%). 86.7% had adapted to the new IC practice guidelines. The respondents reported that they had modified their work practices in several aspects; changes in administrative control, 1,039 (88.3%); enhancing local source control of dental aerosols, 1,031 (87.6%); heightening sterilization and disinfection procedures, 1,032 (87.7%); and improving the ventilation system, 994 (84.5%). As of October 2021, 1,162 (98.7%) respondents were vaccinated, and 47 (3.99%) had tested positive for COVID-19 compared with 2.30% in the general population. Among infected individuals, 10 (21.3%) were suspected of being infected while working in the dental setting. In conclusion, with an average worry score well over 4.10 out of 5, more than 96% of Thai dental professionals reported seeking updated knowledge and agreed that escalation of IC measures was needed. However, only 86.7% improved their COVID-19 infection prevention practices in 4 aspects and appropriate PPE use. The infection rate in dental professionals was 3.99%, with the highest infection rate in dental assistants. Despite statistical insignificance of infection rate between changed and unchanged group, it cannot be concluded that stricter IC measures are negligible as ones might contract disease from setting other than work.